Global graphics color : a guide to design with color for an international market - Peterson, L. K.; Cullen, Cheryl Dangel (Gloucester, Mass. Rockport Publishers, Inc., 2000)
Illustrates how significant color customs are used by different cultures to convey particular meanings to groups of people within that culture.
cat
Keywords: Graphic design; Color in advertising; Visual communication; Architecture